Analisis Struktur Industri Unggulan Terhadap Perkembangan Ekonomi Di Kota Pekalongan Jawa Tengah - Dwi Nur Maulidia; Mohammad Ricko Kurniawan; Muhammad Yasin (Student Research Journal, 2023)
Indonesia in its economic proportion can be categorized as an industrial country. This is because the industrial sector is the largest contributor to the national economy with its contribution reaching more than 20 percent. The manufacturing industry is one of the industries that drives the national economy. Pekalongan City has a very large and iconic manufacturing industry potential. One of the leading industries in Pekalongan city is Batik. The manufacturing industry in batik products is expected to be a strong, resilient, and growing industry. To find out the results, this research will get a lot of learning about the superior industrial strategy of Pekalongan City. To be able to achieve these goals, this research uses descriptive qualitative research methods. In Pekalongan City, the Manufacturing Industry is engaged in 9 sub-sectors of the Processing Industry where the Textile and Textile Products Industry sector will continue to strengthen due to its labor-intensive nature and become a Social Safety Net that supports the income of residents and workers in Pekalongan.